Conflito entre posse funcionalizada e propriedade desfuncionalizada: uma visão constitucional - Telles, Lucio Feres da Silva (2014)
The following essay, which is based on doctrinal and case-law researches, aims to clarify issues regarding the necessity of considering the social role as a condition when pleading ownership and possession matters in court; that is to say, the necessity of a previous verification, made by the Judiciary, regarding the fulfillment of the social role both on ownership and possession, inside repossession and vindicatory suits, as a prerequisite for any judgments over any of these matters. For this purpose, a specific study has been prepared, covering the historical evolution of the ownership and possession concepts is the West, as well as how the Brazilian Federal Constitution of 1988 and the Civil Code handle both of these characters, intending to demonstrate that any judgments regarding ownership and possession depend on complying with the social role, as, considering the wide array of rules which regulate the topic, the so-called social possession should prevail over any possession or ownership that does not fill its social function